Implementasi Supervisi Manajerial Pengawas dalam Meningkatkan Kinerja Guru di MIN 5 Aceh Tenggara - Nasrin, Nasrin (Fitrah: Journal of Islamic Education, 2020)
This paper aims to analyze the implementation of managerial supervision at MIN 5 Aceh Tenggara. This study used a qualitative approach, with a background in the implementation of managerial supervision activities at MIN 5 Aceh Tenggara. Data were collected using in-depth interview techniques, observation and document review. Furthermore, the data were analyzed using data reduction techniques, display or presentation of data and drawing conclusions. The data validity test was carried out by triangulation of sources and methods. The results of this study indicate that the implementation of managerial supervision at MIN 5 Aceh Tenggara is categorized as good, this is indicated by (1) planning aspects, including administrative completeness, observation instruments and classroom learning implementation instruments; (2) implementation aspects, in the form of class observations, private meetings, delivery of results of supervision and follow-up programs of supervision; and (3) the aspect of influence, in the form of creating a "comfortable" learning climate in madrasas.